Effectiveness of Regional Regulation Number 4 Of 2023 Concerning the Empowerment and Protection of Women in the Household in Cirebon Regency - Agusetiyawati, Eka; Dinda , Eka Kurnia; Febriyanti , Indri; Permana, Deni Yusup; Karina , Siska (PT FORMOSA CENDEKIA GLOBAL, 2025)
Violence is an act that is not only dominant in physical form but also in psychological form. Violence against women is an act that is meant to be a violation of human rights, with the existence of gender inequality that results in limited women's rights. To prevent and overcome violence against women, local governments established Regional Regulation (Perda) Number 4 of 2023 concerning Women's Empowerment and Protection. This study aims to analyze the effectiveness of Regional Regulation No. 4 of 2023 in preventing domestic violence against women. The research method used is Empirical Juridical with a sociological and normative approach to observe the application of Regional Regulations in the community. The types of data used are secondary data, including Regional Regulations, statistical data on the annual number of violence cases, and reports on the activities of agencies and institutions. Meanwhile, primary data includes journal books with data collection of interviews with DPPKBP3A and WCC Mawar Balqis as well as the distribution of questionnaires. The study's results show that Regional Regulation No. 4 of 2023 has not been said to be effective because the number of violent incidents is still increasing every year, which is certainly caused by several obstacles, including the availability of infrastructure, law enforcement, and supervision.